Elementary characterization of samples of Portland cement, natural gypsum and phosphogypsum mortars from Brazil (Brazilian Journal of Radiation Sciences, 2019)
Portland cement, the basic ingredient of concrete and is manufactured by crushing, milling and proportioning limestone, sand, clay, iron ore and secondary materials such as shells, chalk or marl combined with shale slate or blast furnace slag, fly ash, gypsum, phosphogypsum, and some others. Evaluating the physical and mineralogical characteristics of the cement and its chemical composition is essential to establish the quality of the product. Therefore, the objective of this work was to characterize and quantify the most common chemical elements in the samples of Brazilian Portland cement, natural gypsum, and phosphogypsum mortars by means of X-ray dispersive energy spectroscopy (EDXRF), as well as to evaluate the strength of these mortars. For analysis of the compressive strength, initially prepared samples were submitted to a destructive mechanical test. Subsequently samples were milled and compacted to form thin tablets, which were submitted to the EDXRF analysis. The qualitative and quantitative analyzes showed that for phosphogypsum mortar the largest mass fractions were found of 49.8±2.5% (Si), 24.66±0.96% (S) and 22.10±0.42% (Ca). For gypsum mortar those values were found of 43.41±0.45% (Ca), 33.8 ± 0.8% (S) and 18.9±1.2% (Si), respectively; and for Portland cement mortar, the predominant elements in those samples have the mass fractions of 64.20±0.52% (Ca) and 27.3±1.5% (Si). The results showed that obtained values of mass fraction of the elements Si, S, K, Ca, Ti, Fe are in rather good agreement with quantities indicated for manufacture. Besides, gypsum and phosphogypsum presented almost the same composition and compressive strength.